Shortages and Challenges in Augmentative Communication through Tangible Interaction using a user-centered design and assessment process - Sanz, Cecilia Veronica (2017)
In this article, we present an assessment process on a tangible interaction application oriented to individuals with complex communication needs, called ACoTI, and details about the main results obtained thus far. The process is based on a set of decisions that have been surveyed as key elements for assessing this type of experiences, based on a background review that was carried out. In addition to that, it has taken into account the contribution of key players from the special education field and it is the foundation for the user-centered and evolutionary design of the application. A number of findings and challenges that open up the door to keep contributing to this specific area was presented. For instance, creating an authoring tool that is available for the educators to be able to generate themselves customized activities for their students, considering the specific needs of each of them.